Whole Organism Model to Study Molecular Mechanisms of Differentiation and Dedifferentiation - Anwar, Areeba (2020)
Cancer recurrence has remained a significant challenge, despite advances in therapeutic approaches. In part, this is due to our incomplete understanding of the biology of cancer stem cells and the underlying molecular mechanisms. The phenomenon of differentiation and dedifferentiation (phenotypic switching) is not only unique to stem cells but it is also observed in several other organisms, as well as evolutionary-related microbes. Here, we propose the use of a primitive eukaryotic unicellular organism, Acanthamoeba castellanii, as a model to study the molecular mechanisms of cellular differentiation and dedifferentiation.